2017
DOI: 10.1080/01616412.2017.1315882
|View full text |Cite
|
Sign up to set email alerts
|

Exercise rehabilitation immediately following ischemic stroke exacerbates inflammatory injury

Abstract: Post-stroke exercise, if too early, may result in elevated levels of cell stress and increased expression of pro-inflammatory cytokines, which may amplify the tissue damage associated with cerebral ischemia/reperfusion injury. The results shed light on the manner in which exercise initiation timing may affect post-stroke rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 38 publications
3
38
0
Order By: Relevance
“…The early improvement in infarct volume seen in these results aligned with a previous meta-analysis, in which infarct volume was reduced most effectively by exercise administered with the shortest delays after ischemia (Egan et al, 2014 ); data from our group derived from pre-conditioning experimentation suggest that this may be related to the capacity of exercise to mitigate inflammatory damage during reperfusion (Ding et al, 2005 ), with the caveat that the exercise initiation too early after ischemia may be detrimental (Li et al, 2017a ). More recent work by our group further substantiated these findings by demonstrating that exercise improved glycometabolism in the ischemic area and decreased neuroinflammation and apoptosis as early as 1 day post-stroke, and also at 3 days (Shen et al, 2016 ; Li et al, 2017a , b , c ). These findings suggest that it is beneficial to initiate exercise early after ischemia/reperfusion, as was done in the present study.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The early improvement in infarct volume seen in these results aligned with a previous meta-analysis, in which infarct volume was reduced most effectively by exercise administered with the shortest delays after ischemia (Egan et al, 2014 ); data from our group derived from pre-conditioning experimentation suggest that this may be related to the capacity of exercise to mitigate inflammatory damage during reperfusion (Ding et al, 2005 ), with the caveat that the exercise initiation too early after ischemia may be detrimental (Li et al, 2017a ). More recent work by our group further substantiated these findings by demonstrating that exercise improved glycometabolism in the ischemic area and decreased neuroinflammation and apoptosis as early as 1 day post-stroke, and also at 3 days (Shen et al, 2016 ; Li et al, 2017a , b , c ). These findings suggest that it is beneficial to initiate exercise early after ischemia/reperfusion, as was done in the present study.…”
Section: Discussionmentioning
confidence: 64%
“…At 3 days of ischemia and reperfusion in rats that underwent MCAO, brains were resected and cut into 2-mm-thick slices, which were then treated with 2,3,5-triphenyltetrazolium chloride (TTC; Sigma–Aldrich, St. Louis, MO, USA) for staining (Li et al, 2017b ), facilitating the use of an indirect method for calculating infarct volume to minimize error caused by edema.…”
Section: Methodsmentioning
confidence: 99%
“…All animals were sacrificed at the same time points: 24 h after forced exercise for detection of infarct volume, 30 min after exercise for quick detection of levels of ATP, NADH and ROS, 24 h for cell death detection, as well as at 3 h and 24 h after exercise termination for later protein expression of angiogenic growth factors. All of the time points for animal sacrifice from this study were based on previous studies (Kochanski et al, 2013; Geng et al, 2016; Shen et al, 2016; Li et al, 2017). The mortality rate was low (less than 10%) and was about equal between paired groups (i.e., stroke groups with or without exercise).…”
Section: Methodsmentioning
confidence: 99%
“…Li et al found that exercise beginning 6–24 h post-stroke led to an increase in inflammatory cytokines, whereas the same exercise commencing 3 days post-stroke decreased those cytokines [43]. Likewise, Risedal et al found that exercise training in rats beginning at 24 h post-stroke was associated with enlargement of ischemic lesions compared with animals who began training at 7 days, though the early and late training groups performed similarly on behavioral tests [44].…”
Section: Neuroplastic Changes Following Strokementioning
confidence: 99%